2007
DOI: 10.1029/2007gl031096
|View full text |Cite
|
Sign up to set email alerts
|

Extreme environments in the forests of Ushuaia, Argentina

Abstract: [1] A survey over two mountain slopes (Glaciar Martial and Cerro Guanaco) in the vicinity of Ushuaia (Tierra del Fuego, Argentina) showed normal results for the region in terms of chlorophyll concentration in the leaves of the dominant tree species Nothofagus antarctica, N. pumilio and N. betuloides, and soil variables such as temperature, moisture, pH, and concentration of nitrogen, sodium and potassium. Solar radiation, on the other hand, showed high values of ultraviolet over the 200 -400 nm range, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…Data of D'Antoni et al [2007] show typical ground‐level solar UV spectra except for dramatic increases in UV‐C radiation, especially as λ approaches 200 nm. These UV‐C fluxes far exceeded those they reported in the UV‐A and UV‐B and were high even in the forest where UV‐A and UV‐B fluxes were low.…”
Section: Uv Radiationmentioning
confidence: 99%
See 3 more Smart Citations
“…Data of D'Antoni et al [2007] show typical ground‐level solar UV spectra except for dramatic increases in UV‐C radiation, especially as λ approaches 200 nm. These UV‐C fluxes far exceeded those they reported in the UV‐A and UV‐B and were high even in the forest where UV‐A and UV‐B fluxes were low.…”
Section: Uv Radiationmentioning
confidence: 99%
“…Even within the instrument's range of maximum sensitivity, significant irradiance near 250 nm was reported. We present calculated irradiance (“tuv” model of Madronich and Flocke [1995]) in Figure 1, along with the 250 nm values of D'Antoni et al [2007] Even using a much lower ozone level in the model than would have occurred on the date of their UV measurements (100 DU instead of 300 DU), the 250 nm values they report exceed the calculated values by more than 15 orders of magnitude. They even considerably exceed the irradiance calculated for zero ozone, and in two cases (CG1 and CG3 at 8 and 12 μ W cm −2 nm −1 , respectively) they surpass the extraterrestrial flux.…”
Section: Uv Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the very method to measure atmospheric ozone content from satellites or from the ground is based on this understanding. (2) Measurements of very high ambient UV radiation have been reported for this region before (D'Antoni et al, 2007(D'Antoni et al, , 2008 but have been shown to be instrument artifacts from stray light (Flint et al, 2008); the extreme UV index values reported by C14 must therefore be taken with additional caution lest a new round of incorrect measurement becomes validation of previously reported mistakes.…”
mentioning
confidence: 99%